The Implementation of Friedman’s Theory in the Context of the Legal System in Indonesia - Febrian,; Nurhidayatuloh; Zuhir, Mada Apriandi; Y, Annalisa (International Journal of Psychosocial Rehabilitation, 2020)
Discussion of the legal system is a complex matter. It is because analyzing the legal system which is applied in a country is not enough just to look at it only from the surface where this is often stated by Indonesian legal scientists who only analyze the legal system only as a form and legal rules without looking at the background of these rules and their relation to society. Therefore, in this paper, it will be discussed comprehensively what and how the legal system in Indonesia runs especially after the reform which happened in 1998. Surely, this is by looking at the context and its implementation using the viewpoint of Lawrence M. Friedman’s Theory. The reason for using this theory is because this theory looks at the legal system with a very comprehensive perspective, especially in the context of the legal system in Indonesia which has high complexity. The method used in this research is the normative legal method using Friedman’s theory. The results of this study are that the legal system is interpreted as a process starting from what is done by legal institutions and how to implement it in the form of actual actions in a social system whose raw materials are from the community, process them and then produce an output that can be applied in society. Then there are three important points of view in examining the legal system in Indonesia, namely legal structure, legal culture, and legal substance that apply in this country.